2007
DOI: 10.4067/s0717-77122007000200014
|View full text |Cite
|
Sign up to set email alerts
|

Parasites of pigeons (Columba livia) in urban areas of lages, Southern Brazil

Abstract: The prevalence of ectoparasites and endoparasites was studied in 58 free-living pigeons (Columba livia) in urban areas of Lages, in the state of Santa Catarina, Brazil. The pigeons were visually inspected and fecal and blood samples were collected to determine the presence of ectoparasites. The serological diagnosis was established through the use of blood smears stained with Quick Panoptic and Giemsa methods. The fecal samples were analyzed using Sheather's method. The Quick Panoptic and Giemsa methods detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
73
2
7

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(87 citation statements)
references
References 10 publications
5
73
2
7
Order By: Relevance
“…Pigeons are related to ancient times and are considered to be cosmopolitan (sari et al, 2008) and pigeons of the columbiforme order are thought to be found in every town and city around the world (Marques et al, 2007). The poultry industry is facing various parasitic diseases of economic importance (Anwar et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pigeons are related to ancient times and are considered to be cosmopolitan (sari et al, 2008) and pigeons of the columbiforme order are thought to be found in every town and city around the world (Marques et al, 2007). The poultry industry is facing various parasitic diseases of economic importance (Anwar et al, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Pigeons are cheap and readily available, which makes them ideal for laboratory and research in Pakistan. Pigeons have close association with other domestic birds, which increases the risk of parasitism and zoonotic disease in human beings (Cooper 1984;Kaninjolo et al, 1988;Piasecki, 2006;Marques et al, 2007;sari et al, 2008). The importance of pigeons can't be ignored because pigeons act as reservoir hosts or carriers and an important source for the infection in birds (Kumar, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the numerous health problems that can affect pigeons, parasite infections may be the most important (MARQUES et al, 2007). Little is known of the species of gastrointestinal parasites that infect these birds (MARQUES et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Little is known of the species of gastrointestinal parasites that infect these birds (MARQUES et al, 2007).…”
Section: Introductionmentioning
confidence: 99%